Analisis Pengaruh Locus Of Control dan Efikasi Diri dalam Program Entrepreneurship di Pondok Pesantren - el Muna, Naily; Agustina, Tiara Putri (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2024)
This research aims to determine the influence of locus of control and self-efficacy in the entrepreneurship program at the Fathul Ulum Jombang Islamic boarding school. This research tries to find out how much influence Locus of control and self-efficacy have in the entrepreneurship program at the Fathul Ulum Jombang Islamic Boarding School. The aim of this research is to analyze the influence of the variables Locus of Control (X1) and Self-Efficacy (X2) on Entrepreneurship (Y). In this research, data was collected using a questionnaire method by distributing Likert scale questionnaires to 60 respondents who were male and female students at the Fathul Ulum Jombang Islamic Boarding School. Then analysis was carried out on the data obtained using quantitative methods. The quantitative analysis used includes validity testing and reliability testing. The data analysis technique used is the multiple linear regression test which functions to prove the research hypothesis. From the results of this analysis, it was found that the independent variable had a positive effect on the dependent variable.